Islam and Israel - Mohsen Saleh (International Institute of Islamic Thought, 1996)
This book consists of six chapters, endnotes, a glossary, a bibliography, and an index. Although fairly short vis-a-vis the long period that it covers (from the Ottoman era to 1988), this book is in fact a very valuable reference work on the subject. The author made considerable efforts to collect, compare, and analyze the data. However, it seems that the main title, Islam and Israel, is rather ambiguous and misleading. The subtitle, Muslim Religious Endowments and the Jewish State, reveals the book's contents adequately. This title may have been coined by the publisher for marketing purposes. The book explores Israeli policy toward Palestinian Muslim religious endowments (awqtif, sing. waqf) and studies the methods employed to confiscate and transfer most of them so that they eventually became exclusively Jewish property. The waqf system played a very significant socioeconomic, religious, and educational role in the history of Muslim society. About 15 percent of the agricultural land in Palestine is waqf (1.2 million dunums), as are many buildings, shops, and other structures in urban areas. The revenue derived from these sources finances important networks of welfare and charitable services in Palestine, such as schools, orphanages, and soup kitchens. The first chapter tackles the Palestinian Muslim waqf system during the late Ottoman empire and the British Mandate. It indicates the importance of waqf for the notable families in Palestine and their administration of it in ways designed to enhance their power and influence. It also studies the arrangements made by the Ottomans during the nineteenth century to set up a waqf administrative structure and to develop it under their close supervision. During the British Mandate (1918-48), however, a new structure, known as The Supreme Muslim Council, was created in 1922. It was dominated by the Palestinian religious elite and notables and took a "national character" under the leadership of Hajj Am1n al ijusayn1. In 1937, the British mandatory government suspended the council's central committee and replaced it with a government-appointed commission. These measures undermined the waqf institution and its role in politics and the national struggle. The second chapter discusses the Muslim waqf system in Israel from 1948 to 1965 and explains how the Zionist state managed to control and confiscate waqf properties and resources. In the parts of Palestine that ...